Resepsi Khalayak Dalam Ruang Komentar Youtube - Yushar, Nur Inayah (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2024)
This study examines netizens' responses to the inaccuracy of the COVID-19 test as Tompi’s claim on Deddy Corbuzier's YouTube channel. The research method adapted Stuart Hall's encoding-decoding model into the online space, and it will analyze the comparison between the discourse that the encoder wants to build with the interpretation built by the decoder. We found some conflicting tendencies. On the one hand, the decoder sometimes articulates what the encoder or sender means and puts some appreciation, making a new story, metaphor, joke, curse word, and opposite interpretation.